1999
DOI: 10.1128/mcb.19.7.5050
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Transcriptional Activation by TATA-Binding Protein and hTAFII28 Requires Specific Amino Acids of the hTAFII28 Histone Fold

Abstract: Coexpression of the human TATA-binding protein (TBP)-associated factor 28 (hTAF II 28) with the alteredspecificity mutant TBP spm3 synergistically enhances transcriptional activation by the activation function 2 of the nuclear receptors (NRs) for estrogen and vitamin D 3 from a reporter plasmid containing a TGTA element in mammalian cells. This synergy is abolished by mutation of specific amino acids in the ␣2-helix of the histone fold in the conserved C-terminal region of hTAF II 28. Critical amino acids are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…The activity of the chimeric product (pG4-ATF7, Figure 1) was assayed in cotransfection experiments with a luciferase reporter gene whose promoter contained five Gal4-binding sites and a TGTA motif in place of the original TATA element. Cos-1 cells were transfected with the following recombinant plasmids: (i) the pG4-ATF7 vector, (ii) a vector encoding a TBP mutant (TBP-spm3) that selectively recognizes the TGTA derivative of the TATA box (Lavigne et al, 1999), (iii) the luciferase reporter and (iv) a vector expressing each of the hsTAFs tested or the corresponding empty vector. The results of a typical experiment are shown in Figure 1.…”
Section: Atf7-induced Transactivation Is Mediated By Hstaf12mentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of the chimeric product (pG4-ATF7, Figure 1) was assayed in cotransfection experiments with a luciferase reporter gene whose promoter contained five Gal4-binding sites and a TGTA motif in place of the original TATA element. Cos-1 cells were transfected with the following recombinant plasmids: (i) the pG4-ATF7 vector, (ii) a vector encoding a TBP mutant (TBP-spm3) that selectively recognizes the TGTA derivative of the TATA box (Lavigne et al, 1999), (iii) the luciferase reporter and (iv) a vector expressing each of the hsTAFs tested or the corresponding empty vector. The results of a typical experiment are shown in Figure 1.…”
Section: Atf7-induced Transactivation Is Mediated By Hstaf12mentioning
confidence: 99%
“…The (17m5)-TK TGTA-Luc reporter (Lavigne et al, 1999) contains the luciferase gene, driven by the thymidine kinase promoter, with an altered TATA box (TGTA, only recognized by the mutant TBP, TBP-spm3 (Lavigne et al, 1999)) and five Gal4-binding sites (see Figure 1).…”
Section: Recombinant Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexpression of TBP and hTAF II 28 shows that they act synergistically to potentiate activation by the VDR or estrogen receptor. This synergism requires specific amino acids of the hTAF II 28 histone fold domain located in the conserved C-terminal half of the protein and can also be abolished by a mutation in the H1Ј helix of TBP (31,32).…”
Section: Transcription Factor Iid (Tfiid)mentioning
confidence: 99%
“…Coexpression of TBP and hTAF II 28 shows that they act synergistically to potentiate activation by the VDR or estrogen receptor. This synergism requires specific amino acids of the hTAF II 28 histone fold domain located in the conserved C-terminal half of the protein and can also be abolished by a mutation in the H1Ј helix of TBP (31,32).Despite its ability to act as a transcriptional coactivator for several NRs, we previously reported that no ligand-dependent interactions with the RXR could be observed (29). In this study, we show that hTAF II 28 does selectively interact with the VDR and thyroid hormone receptor (TR␣) but does so in a ligandreversible manner.…”
mentioning
confidence: 99%